(untitled) (Research, Society and Development, 2023)
Introduction: Inspiratory muscle training (IMT) is used to gain strength and/or inspiratory muscle endurance. However, in children and adolescents with chronic health conditions, studies are scarce, in addition to there being no consensus in the literature regarding its application. Objective: To review the literature regarding the application of IMT in children and adolescents with chronic health conditions. Method: An integrative literature review was carried out in the PubMed, SciELO, Cochrane Library, PEDro, BVS and CAPES databases, selecting clinical trials published from 2010 onwards, which applied IMT without association with other respiratory physiotherapy techniques and with a sample made up of children under 18 years of age with some morbidity. Results: This review included 4 studies published between 2010 and 2021, with samples ranging from 8 to 31 participants, aged 5 to 18 years, who have neurodegenerative, neuromuscular, oncological or post-kidney transplant diseases. Conclusion: IMT proved to be safe and feasible in the reviewed studies and seems to be effective for muscle strengthening, improving functional capacity, lung function and quality of life in these specific populations. However, few studies were found with IMT protocols in the pediatric population, requiring further studies with this specific population.